Immaterial and monetary gifts in economic transactions: Evidence from the field - Michael Kirchler; Stefan Palan (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
Reciprocation of monetary gifts is well-understood in economics. In contrast, there is little research on reciprocal behavior following immaterial gifts like compliments. We close this gap and investigate how employees reciprocate after receiving immaterial and material gifts. We purchase (1) ice cream from fast food restaurants, and (2) durum doner, a common lunch snack, from independent vendors. Prior to the food's preparation, we either compliment or tip the salesperson. Salespersons reciprocate compliments with higher product weight than in a control treatment. This reciprocal behavior grows over repeated transactions. Tips have a stronger level effect which marginally decreases over time.
Keywords: D01; D03; 330; gift exchange; reciprocity; natural field experiment